EphB2-dependent signaling promotes neuronal excitotoxicity and inflammation in the acute phase of ischemic stroke - Ernst, Anne-Sophie; Böhler, Laura-Inés; Hertle, Anna M.; Hoffmann, Angelika; Heiland, Sabine; Sticht, Carsten; Bendszus, Martin; Hecker, Markus; Bading, Hilmar; Marti, Hugo; Korff, Thomas; Kunze, Reiner (Acta Neuropathologica Communications, 2019)
Local cerebral hypoperfusion causes ischemic stroke while driving multiple cell-specific responses including inflammation, glutamate-induced neurotoxicity mediated via NMDAR, edema formation and angiogenesis. Despite the relevance of these pathophysiological mechanisms for disease progression and outcome, molecular determinants controlling the onset of these processes are only partially understood. In this context, our study intended to investigate the functional role of EphB2, a receptor tyrosine kinase that is crucial for synapse function and binds to membrane-associated ephrin-B ligands.
Gesehen am 28.05.2019